Pulmonary Alveolar Microlithiasis: A novel patient and brief review of the literature - de Oliveira Mekonnen, Ariana; Schwerk, Nicolaus; Schütz, Katharina; Schramm, Leonie; Dreissig, Anna; Grewendorf, Simon; Sukdolak, Cinja; Dopfer, Christian; Auber, Bernd; von Hardenberg, Sandra; Happle, Christine (Klinische Pädiatrie, 2022)
Pulmonary Alveolar Microlithiasis (PAM) is a rare hereditary lung disease caused by biallelic pathogenic variants (pV) in the solute family 34 member 2 gene (SLC34A2; Izumi et al., Am J Respir Crit Care Med 2007; 175: 263–268). pVs in this sodium phosphate co-transporter gene lead to accumulation of calcium phosphate crystals within pulmonary alveoli. More than 1000 cases of PAM were thus far reported, with high variance in disease courses (Stamatis et al., Ann Thorac Surg 1993; 56: 972–975). Frequently, asymptomatic cases are observed, and often times slow disease progression until respiratory insufficiency in middle age occurs (Kosciuk, Eur Respir Rev 2020; 29: 200024). Treatment options for PAM are scarce and largely ineffective, and lung transplantation is the only effective therapy in end-stage disease (Stamatis et al., Ann Thorac Surg 1993; 56: 972–975). Here, we report a novel PAM case in an adolescent migrant from East Africa and discuss current diagnostic and therapeutic options.